People, processes, and systems: An observational study of the role of technology in rural youth mental health services. (23rd November 2016) - Orlowski, Simone; Lawn, Sharon; Matthews, Ben; Venning, Anthony; Jones, Gabrielle; Winsall, Megan; Antezana, Gaston; Bidargaddi, Niranjan; Musiat, Peter
Abstract: The merits of technology‐based mental health service reform have been widely debated among academics, practitioners, and policy makers. The design of new technologies must first be predicated on a detailed appreciation of how the mental health system works before it can be improved or changed through the introduction of new products and services. Further work is required to better understand the nature of face‐to‐face mental health work and to translate this knowledge to computer scientists and system designers responsible for creating technology‐based solutions. Intensive observation of day‐to‐day work within two rural youth mental health services in South Australia, Australia, was undertaken to understand how technology could be designed and implemented to enhance young people's engagement with services and improve their experience of help seeking. Data were analysed through a lens of complexity theory. Results highlight the variety of professional roles and services that can comprise the mental health system. The level of interconnectedness evident in the system contrasted with high levels of service self‐organization and disjointed information flow. A mental health professional's work was guided by two main constructs: risk and engagement. Most clients presented with a profile of disability, disadvantage, and isolation, so complex client presentations and decision‐making were core practices. Clients (and frequently, their families) engaged with services in a crisis‐dependent manner, characterized by multiple disengagements and re‐engagements over time. While significant opportunities exist to integrate technology into existing youth mental health services, technologies for this space must be usable for a broad range of medical, psychological and cognitive disability, social disadvantage, and accommodate repeat cycles of engagement/disengagement over time.